A practical procedure to analyze singular configurations in closed kinematic chains - Altuzarra, O.; Pinto, C.; Aviles, R.; Hernandez, A. (IEEE transactions on robotics, 2004)
The authors present a general method for the automated singularity analysis of any mechanism at a given configuration. The procedure uses a base of the motion space. This is obtained from a velocity equation characterized by a geometric matrix. This special form of Jacobian matrix has some advantages for automatic implementation. This approach provides the degree of freedom associated with the singularity, uncontrolled motion, and kinematic dependencies. It also facilitates the choice of actuators and redundant devices. The method has been implemented in a computer program for kinematic analysis.